Performance of organics and nitrogen removal in subsurface wastewater infiltration systems by intermittent aeration and shunt distributing wastewater. (July 2016) - Pan, Jing; Yuan, Fang; Yu, Long; Huang, Linli; Fei, Hexin; Cheng, Fan; Zhang, Qi
Highlights: Intermittent aeration created favorable aerobic conditions for nitrification. Shunt wastewater supplied carbon sources for denitrification. Intermittent aeration and shunt wastewater combined distinctly enhanced TN removal. Intermittent aeration and shunt wastewater combined provided an option for SWISs. Abstract: Organics and nitrogen removal in four subsurface wastewater infiltration systems (SWISs), named SWIS A (without intermittent aeration and shunt distributing wastewater), SWIS B (with intermittent aeration), SWIS C (with shunt distributing wastewater) and SWIS D (with intermittent aeration and shunt distributing wastewater) was investigated. High average removal rates of 92.3% for COD, 90.2% for NH4 -N and 88.1% for TN were achieved simultaneously in SWIS D compared with SWIS A, B and C. The excellent TN removal of SWIS D was due to intermittent aeration provided sufficient oxygen for nitrification in upper matrix and the favorable anoxic or anaerobic environment for denitrification in subsequent matrix, and moreover, shunt distributing wastewater provided sufficient carbon source for denitrification process. The results indicated that intermittent artificial aeration combined with shunt distributing wastewater could achieve high organics and nitrogen removal in SWISs.